2010
DOI: 10.1111/j.1600-0536.2009.01657.x
|View full text |Cite
|
Sign up to set email alerts
|

Linalool – a significant contact sensitizer after air exposure

Abstract: Raising the patch test concentration for ox. linalool gave a better detection of contact allergy, as many as 5-7% positive patch test reactions were detected. We suggest a patch test concentration of ox. linalool 6.0% pet. for future patch testing, giving a dose per unit area of 2.4 mg/cm(2) when 20 mg test substance is tested in small Finn Chambers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
106
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(122 citation statements)
references
References 36 publications
(66 reference statements)
15
106
0
1
Order By: Relevance
“…Regarding sensitization, no patients were, to our knowledge, actively sensitized during the present study, as no cases of late‐appearing reactions were reported. On the basis of these results, and according to previous recommendations , it seems that patch test preparations of Lim‐OOHs 0.3% pet. and Lin‐OOHs 1.0% pet.…”
Section: Discussionsupporting
confidence: 64%
“…Regarding sensitization, no patients were, to our knowledge, actively sensitized during the present study, as no cases of late‐appearing reactions were reported. On the basis of these results, and according to previous recommendations , it seems that patch test preparations of Lim‐OOHs 0.3% pet. and Lin‐OOHs 1.0% pet.…”
Section: Discussionsupporting
confidence: 64%
“…In a study of 1511 dermatitis patients, auto-oxidized linalool was shown to induce allergenic responses in 1.3 % of those tested, with 1.1 % of patients sensitive to the linalool hyperoxide fraction, using patch tests [23]. A follow-up study, again involving 1511 dermatitis patients, showed that exposure to oxidized linalool at concentrations of > 6.0 % resulted in allergenic irritation in 5-7% of test subjects [24]. Given the allergenic nature of some of the constituents of lavender essential oil and their breakdown products, as well as an increasing awareness of their presence in cosmetics and aroma-therapeutic products, future research directed towards understanding the potential allergenic properties of commonly used monoterpenoids, and their breakdown products, is critical to ensure their safe usage.…”
Section: Studies In Human Subjectsmentioning
confidence: 99%
“…This may lead to shifting color, an increase in viscosity or the formation of an unpleasant, often pungent aroma by changes in composition and a rise of oxidized compounds, the so-called "off-flavor". Moreover, terpenoid oxidation products may even cause allergic skin reactions while their non-oxidized counterparts are not or only scarcely irritating (Bråred-Christensson, Forsström, Wennberg, Karlberg, & Matura, 2009Bråred-Christensson, Matura, Gruvberger, Bruze, & Karlberg, 2010;Hagvall et al, 2007;Hausen, Reichling, & Harkenthal, 1999;Matura et al, 2005;Pirilä & Siltanen, 1958). Nevertheless, only few studies have been performed to comprehensively assess the impact of storage conditions on the stability of essential oils (Braun & Franz, 1999;ElNikeety, El-Akel, Abd El-Hady, & Badei, 1998;El-Wakeil et al, 1986;Fincke & Maurer, 1974;Haddouchi, Chaouche, Lazouni, & Benmansour, 2011;Misharina & Polshkov, 2005;Misharina, Polshkov, Ruchkina, & Medvedeva, 2003;Nguyen et al, 2009;Tóth, 1967), while HPLC was hitherto not addressed in this regard except for quantification of selected hydroperoxides (Hagvall, Sköld, Bråred-Christensson, Börje, & Karlberg, 2008).…”
Section: Introductionmentioning
confidence: 99%